2012
DOI: 10.1016/j.bbamcr.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 17 inhibits myogenic and promotes osteogenic differentiation of C2C12 myoblasts by activating ERK1,2

Abstract: The present study evaluated the role of interleukin (IL) 17 in multilineage commitment of C2C12 myoblastic cells and investigated associated signaling pathways. The results concerning the effects on cell function showed that IL-17 inhibits the migration of C2C12 cells, while not affecting their proliferation. The data regarding the influence on differentiation demonstrated that IL-17 inhibits myogenic differentiation of C2C12 cells by down-regulating the myogenin mRNA level, myosin heavy chain expression and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 50 publications
5
37
1
Order By: Relevance
“…In this line, IL-17 was shown to trigger numerous signal transduction pathways, including ERK1/2 and p38 MAPKs [4]. In accordance with our previous work [19], we confirmed here that IL-17 is able to enhance phosphorylation of ERK1/2 in C2C12 cells, and we also showed that this pathway was essential for the induction of MMP-9 expression by IL-17. Our results indicate that Doxycycline strongly inhibits IL-17-induced MMP-9 expression and ERK1/2 activation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this line, IL-17 was shown to trigger numerous signal transduction pathways, including ERK1/2 and p38 MAPKs [4]. In accordance with our previous work [19], we confirmed here that IL-17 is able to enhance phosphorylation of ERK1/2 in C2C12 cells, and we also showed that this pathway was essential for the induction of MMP-9 expression by IL-17. Our results indicate that Doxycycline strongly inhibits IL-17-induced MMP-9 expression and ERK1/2 activation.…”
Section: Discussionsupporting
confidence: 92%
“…We have previously shown that IL-17 activates ERK1/2 in C2C12 cells [19], and, in order to clarify whether ERK1/2 pathway mediates IL-17-induced MMP-9 production and expression, C2C12 cells were treated with IL-17 in the presence of MEK1,2 inhibitor, PD98059, and the MMP-9 protein and mRNA expression were determined. As shown in Figure 5(a), cotreatment of the cells with IL-17 and MEK1,2 inhibitor significantly blocked the increment of both MMP-9 activity and mRNA expression induced by IL-17.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-17F also stimulated osteogenic differentiation of MC3T3-E1 mouse pre-osteoblast cells, as well as primary mouse mesenchymal stromal cells (29). In mouse myoblast cell line C2C12, IL-17 promoted osteogenic differentiation, while suppressing myogenic differentiation (30). Interestingly, IL-17 has been widely accepted to inhibit adipogenesis (31), suggesting that IL-17 may steer mesenchymal stem cells into an osteogenic fate (Fig.…”
Section: Il-17 and Bone Metabolismmentioning
confidence: 85%
“…While IL-17 alone had no effect on CCL20 production, IL-17 amplifiedthe effects of IL-1βon IL-6 and CCL20 secretion by the muscle explants.In another study the expression of HLA class I, CFos, NF-κB and C-Jun was also found to be increased by IL-17 stimulation [106]. A recentstudy demonstrated the ability of IL-17 to inhibit myoblast migration and myogenic differentiation in an ERK1,2 dependent manner [107].In a further study IL-17 was shown to mediate this effect though the inhibition of urokinase type plasminogen inhibitor (uPA), a key molecule in skeletal myogenesis [108].…”
Section: Actions Of Il-17 On Musclementioning
confidence: 94%